The Effect of Using Crankcase Emission Control System Technology on the Performance of a 160 cc Single Cylinder Four Stroke Engine - Yanatra Budi Pramana; Arifin, Syamsul (Tibuana, 2024)
The research was carried out on a single-cylinder four-stroke petrol engine with a rotation variation of 1000 rpm - 9000 rpm, using crankcase emission control system (CECS) technology. The air that will enter the carburetor is mixed with hot gas that flows and comes from the CECS, causing the air to become warm and then mixed with the fuel in the carburetor and then the mixture passes through the manifold into the combustion chamber. Investigation in the first stage under standard conditions and in the second stage using CECS technology. The use of CECS technology results in increased machine performance. After testing with and without using CECS technology, optimum performance in the form of power, torque and specific fuel consumption occurred at engine speeds of 8000 rpm, 6000 rpm and 7000 rpm respectively producing power, torque and specific fuel consumption of 13.11 ; 1.504 kg.m and 0.152 kg/hp.hour without CECS, and with the use of CECS technology of 13.20 hp; 1.56 kg.m and 0.151 kg/hp.hour.